Perancangan Prototype Aplikasi Pemesanan Makanan Sehat Berbasis Mobile Menggunakan Metode Design Sprint - Febriana Akbar, Rizky; Saptono, Henry; Rustianto, April (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
With the advancement of technology and information in the current digital era, public awareness of the importance of a healthy diet continues to increase. To meet this need, the author uses Figma design tools to create a healthy food ordering mobile application solution that follows the latest trends. The design sprint method is applied as a rapid approach to problem-solving and as a guide in the interface design process of the application. This research involves interviews and surveys to understand user needs. Usability testing was conducted using the System Usability Scale (SUS), which yielded a score of 73, indicating that the application prototype is feasible based on objective assessments. The conclusion of this Final Project is that the application prototype was designed using the design sprint method, encompassing five stages, and effectively designing seventeen application screens.